PRACTICE AND MAIN STAGES OF DEVELOPMENT OF TECHNICAL CYBERNETICS - Blokhin, L. N.; Osadchy, S. I. (Problems of Informatization and Management, 2021)
A subjective view of the historical stages in the development of technical cybernetics as a science aimed at effectively meeting the various urgent needs of the practical life of society is presented. It is believed that the above provisions will help the present young generation of scientists and practitioners to orient themselves more correctly in the stormy sea of modern management theories that differ in their effectiveness.